Effect of Deep Heating and Foam Rolling vs. Static Stretching of the Gastrocnemius and Soleus Complex in Improving Active Ankle Dorsiflexion Range of Motion - Ericson, Melissa; Kennedy, Amy; Rosentreter, Karlee (My University, 2015)
The purpose of this study was to determine which treatment protocol involving static stretching, deep heating, and/or foam rolling would provide greater improvements in ankle dorsiflexion range of motion.
Color poster with text, tables, and photographs.
Keywords: Bilateral dorsiflexion; Foam rolling; Gastrocnemius; Functional Movement Screening (FMS); Range of motion (ROM); Posters